1995
DOI: 10.1126/science.7569928
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Tyrosine-Based Sorting Signals with Clathrin-Associated Proteins

Abstract: Tyrosine-based signals within the cytoplasmic domain of integral membrane proteins mediate clathrin-dependent protein sorting in the endocytic and secretory pathways. A yeast two-hybrid system was used to identify proteins that bind to tyrosine-based signals. The medium chains (mu 1 and mu 2) of two clathrin-associated protein complexes (AP-1 and AP-2, respectively) specifically interacted with tyrosine-based signals of several integral membrane proteins. The interaction was confirmed by in vitro binding assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
880
1
17

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 911 publications
(929 citation statements)
references
References 32 publications
31
880
1
17
Order By: Relevance
“…The β-subunit of AP-2 also interacts with clathrin and is able to promote clathrin lattice assembly (36). The μ-subunit of AP-2 recognizes the tyrosine-based internalization signals within the cytoplasmic domain of some receptors (37), while the function of the σ chain remains unclear. Both α-and β-subunits of AP-2 are shown to interact with CXCR2 in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The β-subunit of AP-2 also interacts with clathrin and is able to promote clathrin lattice assembly (36). The μ-subunit of AP-2 recognizes the tyrosine-based internalization signals within the cytoplasmic domain of some receptors (37), while the function of the σ chain remains unclear. Both α-and β-subunits of AP-2 are shown to interact with CXCR2 in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Basolateral sorting is guided by basolateral sorting signals (Keller and Simons, 1997;Rodriguez-Boulan et al, 2005), and they include: short tyrosine motifs such as Yxxf or NPXY (Brewer and Roth, 1991;Le Bivic et al, 1991;Matter et al, 1992), dileucine (Hunziker and Fumey, 1994) or monoleucine motifs with nearby acidic patches (Deora et al, 2004), PxxP, found in EGFR and pleomorphic motifs that do not yet fall into established classes, found in NCAM (Le Gall et al, 1994), transferrin receptor (Odorizzi and Trowbridge, 1997) and polymeric IgA receptor (Aroeti and Mostov, 1994) ( Figure 2). Yeast 2 and 3 hybrid assays (Ohno et al, 1995;Janvier et al, 2003) demonstrated that Yxxf motifs interact with the m subunit of AP adaptors (AP1, AP2, AP3, AP4), whereas dileucine motifs of the type [DE]XXXL [LI] bind to g and s1 subunits of AP1 and to d and s3 subunits of AP3 (Kirchhausen, 2000;Bonifacino and Traub, 2003). Crystallographic studies have elucidated details of some of these interactions, for example, of the AP m subunits with tyrosine motifs and of GGAs (Golgi-localized, g-ear containing, Arf-binding protein) with dileucine motifs in Man6PR (Bonifacino, 2004;Owen et al, 2004).…”
Section: Polarized Trafficking Machinerymentioning
confidence: 99%
“…Tyrosine-containing motifs in the C-terminal tails of the receptors for epidermal growth factor, asialoglycoproteins and polymeric immunoglobulins interact directly with the clathrin-associated adaptor protein complex AP-2 [167,168]. The µ2-chain of AP-2 interacts with the Ser-Asp-Tyr-Gln-Arg-Leu motif of the Cterminal tail of the integral membrane protein TGN38 (TGN l trans-Golgi network), as well as with similar motifs from lamp-1, CD68, H2-Mb (histocompatibility Class 2 gene Mb) and the transferrin receptor [169]. The importance of this interaction has recently been questioned by the finding that deletion of the AP-2 binding site of the epidermal growth factor receptor abolishes AP-2 binding to the receptor without affecting internalization [170].…”
Section: Domains Involved In Receptor Endocytosismentioning
confidence: 99%